Value co-creation in asset integrity and improvement portfolio: evidence from the Australian mining industry. Issue 2 (11th August 2021) - Lawson, Brenton; Statsenko, Larissa; Shokri-Ghasabeh, Morteza
Abstract : Purpose: Adopting a qualitative research design and following a single case study research methodology 21 semi-structured interviews with asset integrity project managers (PM), project sponsors (PS) and members of the project management office (PMO) were conducted. These were complemented with company's project management framework documents and tools and direct observation by the researcher's observation. Design/methodology/approach: The data on the value creation in the mining asset integrity and improvement project portfolio was collected through 21 interviews with PM, PS and members of the PMO and complemented by observational data and the analysis of the Australian mining company process documentation. Findings: The study finds that establishing a culture of delivering value supported by functional governance is critical for effective value creation practice in asset integrity and improvement project portfolios. In addition, early engagement of the key stakeholders with clearly defined roles and utilisation of project value management artifacts, enables effective value delivery throughout the project lifecycle. Originality/value: The research offers an empirically grounded framework to facilitate value creation throughout the project lifecycle in asset integrity and improvement project portfolios drawing on a benchmarking case of an Australian mining company.